HIV-1, methamphetamine and astrocytes at neuroinflammatory Crossroads - Borgmann, Kathleen; Ghorpade, Anuja (Frontiers in Microbiology, 2015)
As a popular psychostimulant, methamphetamine (METH) use leads to long-lasting, strong euphoric effects. While METH abuse is common in the general population, between 10 and 15% of human immunodeficiency virus-1 (HIV-1) patients report having abused METH. METH exacerbates the severity and onset of HIV-1-associated neurocognitive disorders (HAND) through direct and indirect mechanisms. Repetitive METH use impedes adherence to antiretroviral drug regimens, increasing the likelihood of HIV-1 disease progression toward AIDS. METH exposure also directly affects both innate and adaptive immunity, altering lymphocyte numbers and activity, cytokine signaling, phagocytic function and infiltration through the blood brain barrier. Further, METH triggers the dopamine reward pathway and leads to impaired neuronal activity and direct toxicity. Concurrently, METH and HIV-1 alter the neuroimmune balance and induce neuroinflammation, which modulates a wide range of brain functions including neuronal signaling and activity, glial activation, viral infection, oxidative stress, and excitotoxicity. Pathologically, reactive gliosis is a hallmark of both HIV-1- and METH-associated neuroinflammation. Significant commonality exists in the neurotoxic mechanisms for both METH and HAND; however, the pathways dysregulated in astroglia during METH exposure are less clear. Thus, this review highlights alterations in astrocyte intracellular signaling pathways, gene expression and function during METH and HIV-1 comorbidity, with special emphasis on HAND-associated neuroinflammation. Importantly, this review carefully evaluates interventions targeting astrocytes in HAND and METH as potential novel therapeutic approaches. This comprehensive overview indicates, without a doubt, that during HIV-1 infection and METH abuse, a complex dialog between all neural cells is orchestrated through astrocyte regulated neuroinflammation.